The relation between mining sector and economic growth in Peru during the periods 1992-2016 - Ibanez Quispe, Medally (2018)
The purpose of this thesis is to investigate whether imperative results about dynamic relations between economic growth and mining sector variables are valid in a small open economy such as the Peruvian. Using time series econometric approaches like cointegration technique and Vector Error Correction Model (VECM) on annual data from 1992 to 2016. The author examines how the Real GDP, mining investments, mining exports and mining sector growth, simultaneously affects one each other in the long and short-run. The present study is made on secondary data retrieved from the Central Reserve Bank of Peru (BCRP) and Ministry of Energy and Mines of Peru (MINEM).